Equatorial Guinea's Fang Woman between modernization and Tradition - Giordano, Maria Laura; Ayíngono Edu Nchama, María Soledad (Res Publica. Revista de Historia de las Ideas Políticas, 2025)
This study aims to shed light on the historical causes of social underestimation for women in Equatorial Guinea, attempting to unravel the socio-cultural dynamics that stranded them in a factual inferiority in force until today. The reflection we will carry out in these pages tries to identify the cultural elements of the fang tradition that objectify women, ―some tribal rituals, especially those related to the polygamy and dowry― as well as to isolate possible historical causes and their perverse effects on women and society. Fang culture has been able to keep women in complete submission, perhaps due to an extrapolation of the colonial model, transferred to male-female paradigm of relations.
Keywords: fang women; contemporary history; social underestimation; patriarchate; decolonial thinking